Method for constructing a two-picture 6-parameter nomogram - Nurmakhanov Баймахан; Bektibaeva Зияш (Рroblems of engineering and professional education, 2023)
Components large esepteletin 5 құramadan turatyn zattyң қasietterinіn өzgeruіn anyқtaityn nomogram salu zholy ұsynylғan. Nomogram of tazhіribelіk synak қorytyndylary nәtizhelerі boyinsha salynada.